ELABORASI TENTANG PELAYANAN DAN TANGGUNG JAWAB KEPADA PASIEN DI PUSKESMAS TEGALREJO SALATIGA - Sari, Irine Diana (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2023)
This study aims to determine the level of service and responsibility to patients provided by the Tegalrejo Salatiga Community Health Center and to determine the relationship between service and responsibility provided by the Tegalrejo Salatiga Community Health Center. Based on the results of the analysis regarding the Elaboration of Services and Responsibilities to Patients at the Tegalrejo Salatiga Health Center, it was found that the level of service and responsibility to patients provided by the Tegalrejo Salatiga Health Center was good, acceptable (proven), because it was based on the mean value of the level of service and responsibility to patients showed that the mean value of service level was 7.0900 and the mean value of responsibility to patients was 6.9710. The average values ​​(mean) 7.0900 and 6.9710 are in the interval 6.37-7.27 (good). So it can be concluded that the Tegalrejo Salatiga Community Health Center has a good level of service and responsibility to patients. The hypothesis which states that there is a significant positive relationship between the service and responsibility to patients provided by the Tegalrejo Salatiga Community Health Center is accepted (proven). Because the value of χ2count (150.886) > χ2table (43.773), and the value of Contingency Coefficient C (0.776) ≠ 0, then H0 is rejected and Ha is accepted.